(untitled) (Research, Society and Development, 2021)
Wheat flour is often used to prepare confectionery and baked goods, however, it can be contaminated by aporulating microorganisms contaminated during harvest or improper storage. The aim of this study was to isolate Bacillus cereus strains from different wheat flour brands and to evaluate their thermoresistance in different confectionery products. It was done in order to investigate the risks posed by food prepared with flour contaminated with B. cereus to consumers’ health. The investigation of B.cereus was realized in five brands of different wheat flours were collected and named A to E. The isolated strains were subjected to boiling tests in vitro to evaluate their thermoresistance. In addition, confectionery products were prepared with flour contaminated with B. cereus strains. These products were subjected to different cooking and B. cereus strain ATCC®30301™ was used as control. Flour brands were contaminated with B. cereus; and counts ranged from 0.25 to 1.57 log CFU/g. The strains presented higher thermoresistance in the confectionery products than in the test conducted in vitro. Based on our results, it was concluded that B. cereus strains are thermoresistant. Moreover, if the flour is contaminated with this bacterium, food products subjected to thermal treatments may remain contaminated. In addition, it is suggested that there is some mechanism (not observed in our study) that could directly influence the thermoresistance of strains found in food.